Are KIF6 and APOE polymorphisms associated with power and endurance athletes?. Issue 9 (2nd September 2021) - Wojciechowicz, Bartosz; Laguette, M.-J. Nancy; Sawczuk, Marek; Humińska-Lisowska, Kinga; Maciejewska-Skrendo, Agnieszka; Ficek, Krzysztof; Michałowska-Sawczyn, Monika; Leońska-Duniec, Agata; Kaczmarczyk, Mariusz; Chycki, Jakub; Trybek, Grzegorz; September, Alison V.; et al.
Abstract: Genetic polymorphisms within physiologically relevant KIF6 and APOE genes were examined in the context of athletic performance. KIF6 and ApoE are involved in cardiovascular health, modulation of lipid level and neurotransmission amongst others. The aim of this study was to examine whether three polymorphisms, KIF6 rs20455T > C, APOE rs429358T > C and APOE rs7412 C > T, were associated with athletic status of an athlete defined as performance type (endurance or power). Genotyping was performed using real-time PCR on buccal genomic DNA from 204 Polish athletes including 104 endurance and 100 power athletes, and 161 sedentary individuals. APOE rs429358 genotype frequencies differed significantly between power athletes and sedentary individuals ( p  = 0.046). KIF6 rs20455 and APOE rs7412 were found to be epistatically associated with the power athletic status ( p  = 0.032). KIF6 rs20455, APOE rs429358 and APOE rs7412 were associated with athletic status of Polish athletes. In the future, these polymorphisms could contribute to predictive models aimed at assessment of an individual's athletic status.